1974
DOI: 10.1111/j.1939-0025.1974.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of college students as therapeutic agents with chronic hospitalized patients.

Abstract: This paper assesses the therapeutic effectiveness of college students working with chronic, hospitalized mental patients. Significant improvement in be havior was found for the patients in the experimental group on the Paranoid Projection, Anxious Intropunitiveness, and Conceptual Disorganization sub scales of the Inpatient Multidimensional Psychiatric Scale. Male patients showed more improvement than did females working with the female college students in the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Previous research showing the effectiveness of student programs used indirect measures of behavior such as psychological tests (Holtzberg, et al, 1966;Poser, 1966), or interviews (Bergman & Doland, 1974), whereas the present study used more direct measures of behavior and showed statistically significant differences between experimental and control patients.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Previous research showing the effectiveness of student programs used indirect measures of behavior such as psychological tests (Holtzberg, et al, 1966;Poser, 1966), or interviews (Bergman & Doland, 1974), whereas the present study used more direct measures of behavior and showed statistically significant differences between experimental and control patients.…”
Section: Discussionmentioning
confidence: 68%
“…The. questionnaire included 9-point rating scales and various open-ended questions and was identical to a questionnaire used in a previous study (Bergman & Doland, 1974). Using the Kolmogorov Smirnov one-sample test (Siegel, 1956), results from the first question indicated that students viewed changes in patient behavior since the beginning of the program (Jr = 6.18, D(43) = 0.33, p<.01).…”
Section: Effects Of the Program On The Studentsmentioning
confidence: 98%
See 3 more Smart Citations